Customer Relationship Management Gadjah Mada University Club Hotel In Building Customer Loyalty - Fauzan, Moh. (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The development of the hospitality business in Yogyakarta has grown every year. This creates business competition in the hospitality industry which requires business people to make strategies to be able to compete with other competitors. Seeing the potential that Yogyakarta has as a tourism city, Gadjah Mada University (UGM) also takes part in this matter, through the Gadjah Mada University Club Hotel (UC Hotel UGM) which has MICE (Meeting, Incentive, Conference, and Exhibition) which is so strategically located in the center of Yogyakarta and is in the middle of UGM campus. This makes UC Hotel UGM need to set a strategy to be able to compete in the surrounding hotel business market in order to attract customer loyalty. This research aims to find out how Customer Relationship Management (CRM) at UC Hotel UGM builds customer loyalty. This study uses descriptive qualitative research methods using interview, observation and document data collection techniques. The results of the study show that eight elements of CRM can help hotels build relationships with customers, increase customer loyalty, and build a better hotel reputation. However, to maintain customer loyalty at UC Hotel UGM Yogyakarta, it is advisable to implement CRM consistently and always evaluate regularly and continuously to create a sense of satisfaction for the customer himself in order to build customer loyalty. CRM activities that have been carried out by UC Hotel UGM have been running well, which can be seen from customers who feel customer relations activities while at UC Hotel UGM and positive reviews through google maps.